The phytochemistry and pharmacology of medicinal fungi of the genus Phellinus: a review. Issue 5 (12th February 2021) - He, Pingya; Zhang, Yi; Li, Ning
Abstract : A comprehensive review on secondary metabolites with bioactivities from 13 Phellinus species. Abstract : Phellinus Quél is one of the largest genera of Hymenochaetaceae, which is comprised of about 220 species. Most Phellinus macro-fungi are perennial lignicolous mushrooms, which are widely distributed on Earth. Some Phellinus fungi are historically recorded as traditional medicines used to treat various diseases in eastern Asian countries, especially China, Japan and Korean. Previous phytochemical studies have revealed that Phellinus fungi produce diverse secondary metabolites, which mainly contain polysaccharides, flavones, coumarins, terpenes, steroids, and styrylpyranones. Pharmacological documents have demonstrated that Phellinus mushrooms and their compounds have a variety of bioactivities, such as anti-tumor, immunomodulation, anti-oxidative and anti-inflammation, anti-diabetes, neuro-protection, and anti-viral effects. This review surveys the literature reporting the isolation, characterization, and bioactivities of secondary metabolites from the fungi of the genus Phellinus, focusing on studies published in the literature up to April 2020. Herein, a total of more than 300 compounds from 13 Phellinus species and their isolation, characterization, chemistry, pharmacological activities, and relevant molecular mechanisms are comprehensively summarized.